2010
DOI: 10.1007/s00167-010-1104-6
|View full text |Cite
|
Sign up to set email alerts
|

Opening-wedge high tibial osteotomy without bone graft

Abstract: Open wedge high tibial osteotomy has become the trend for correction of varus knee deformities. The drawbacks were the need of autogenous bone graft with its associated morbidity, and later the use of bone substitutes with their cost and delayed healing. In this study, a total of 58 consecutive patients underwent high tibial osteotomy with internal fixation by wedge (toothed) plate and screws without bone graft, from 2004 to 2008. Age of the patients ranged from 24 to 65 years. There were 37 women and 21 men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
(56 reference statements)
4
67
0
1
Order By: Relevance
“…With regard to clinical relevance, this study supported the reasonableness of the most frequently used target of limb alignment after HTO, which is a femorotibial angle of 170° or a mechanical axis crossing the tibia plateau at 62 % from the medial edge of the tibial plateau to its entire width [3,6,7,23,24], because no significant differences were observed in terms of the ratio of cartilage repair in the medial compartment of the femorotibial joint.…”
Section: Discussionmentioning
confidence: 85%
“…With regard to clinical relevance, this study supported the reasonableness of the most frequently used target of limb alignment after HTO, which is a femorotibial angle of 170° or a mechanical axis crossing the tibia plateau at 62 % from the medial edge of the tibial plateau to its entire width [3,6,7,23,24], because no significant differences were observed in terms of the ratio of cartilage repair in the medial compartment of the femorotibial joint.…”
Section: Discussionmentioning
confidence: 85%
“…Earlier studies pointed to a concern about the risk of nonunion with this approach [20,23], whereas some more recent work has suggested that the risk of nonunion for opening wedge HTO is not higher than that for the closed wedge technique [3,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…3,6,20 A vacant osteotomy gap has been reported to remain stable with locking plate fixation, without implant failure. 2,9 However, some studies have reported complications, including correction loss and screw breakage. 8,9 The method of gap filling using an autologous bone graft is considered as the gold standard approach.…”
Section: Discussionmentioning
confidence: 99%
“…2,9 However, some studies have reported complications, including correction loss and screw breakage. 8,9 The method of gap filling using an autologous bone graft is considered as the gold standard approach. 21,22 However, in the process of harvesting the bone, several issues, such as donor-site pain, meralgia paresthetica, increased blood loss, increased operation time, and potential for donor-site infection, might occur.…”
Section: Discussionmentioning
confidence: 99%